Jelena J. Dimitrijević’s American Scope of Topics in Teaching (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The paper sheds light on the methodological conveniences that can be achieved in teaching by studying the works from Jelena J. Dimitrijević’s American scope of topics. The analysis of representative reformed teaching plans and programs shows that they are progressive in terms of their theoretical formulations, but not in terms of their very content. The paper explains the educational outcomes, standards, competences, teaching goals, methods, and principles that can be achieved in a classroom interpretation of Jelena J. Dimitrijević’s works. It re-evaluates the methodological activities (motivation, interpretation, and localization) and correlations that are used in the classroom examination of works by this Serbian modernist woman author. Finally, the paper offers a methodological suggestion for research assignments and the dynamics of interpretation of “The American Woman” story.
Keywords: Jelena J. Dimitrijević; modernism; Serbian language; Serbian literature; teaching methodology; gynocriticism